Legal right to damages in accident cases:Employer's duty to visitors to property - Abdul Rahman, Rozanah; Sufian, Azlinor (National Institute of Occupational Safety and Health (NIOSH), 2007)
Accident cases in the property of the employer may involve members of the public including the licensees and the invitees. The status of a visitor as a licensee or an invitee defines the legal rights of the visitor if they are injured due to the negligence of the occupier of the property. Therefore, where licensees or invitees are present, the occupier has a duty to make the property safe for the licensees or the invitees. A duty to warn arises if there is harmful condition on the land and any activity conducted on the land by or at the behest of the owner of the land must be conducted with the care that a prudent person would show. As this paper seeks to elucidate the duties owed by the employer as the occupier of a property to the visitors, the legal analysis also seeks to identify the legal right to damages available to the visitors who sustain injuries due to accidents taken place in the property of the employer.